Hearts of steel [large type] - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Blackstone legacy, 2023)
"Maggie Molinaro survived a hardscrabble childhood in the downtrodden streets of Manhattan to become a successful businesswoman. After a decade of sacrifice, she now owns a celebrated ice cream company, but when she offends a corrupt banker, she unwittingly sets off a series of calamities that threaten to destroy her life's work. Liam Blackstone is a charismatic steel magnate committed to overhauling factory conditions for the steelworkers of America. Standing in his way is the same villain determined to ruin Maggie. What begins as a practical alliance to defeat a common enemy soon evolves into a romance between two wounded people determined to beat the odds. A spiraling circle of treachery grows increasingly dangerous as Liam and Maggie risk their lives and fortune for the good of the city. It will require all their wit and ingenuity to navigate the dangerous waters ahead, but their crusade could cost them everything. Return to New York City for another dramatic and romantic story from the enchanted pen of bestselling author Elizabeth Camden"--